Research on 5G service coverage capability before 4G carrier re-farming to 5G - Guanghai LIU; Tian XIAO; Bei LI; Xinzhou CHENG; Yongbei XUE; Yi LI; Xiaomeng ZHU; Yuting ZHENG (Dianxin kexue)
In order to build a low-cost and high-efficiency 5G low-frequency network, it is necessary to study the best plan of plowing low-frequency 3G and 4G networks into 5G in advance.Under the condition of no ideal low frequency 5G test environment due to no re-farming, the coverage capacity after re-farming was estimated through theoretical analysis and was indirectly verified based on the current network test data.The key setting of link budget and model selection were discussed, the rationality of the estimation results was indirectly verified by the actual test data.The conclusion had been actually applied to the planning scheme of a major operator for the national 900 MHz network, which has essential reference significance to guide the network refarming.